Electrical impedance response for physical simulations of composites with conductive fiber-bridged insulating cracks - S. Wansom (2018)
© 2017, Springer Science+Business Media New York. Physical simulations of cement-based composites containing “fiber-bridged cracks” were prepared using insulating right cylindrical plastic discs at a fixed volume fraction and each disc was pierced through by different numbers and/or different lengths of perpendicular steel fibers. All the discs were z-axis aligned, with the axis of rotation of the disc parallel to the z-axis of the sample, and placed at random positions within the composites. The conductivity of the composites were measured by AC-impedance spectroscopy (AC-IS) to quantitatively separate the effects of the conductive fibers and insulating cracks on the composite conductivity when they coexist in a large number. Using a known orientation of both inclusions, in the form of “fiber-bridged cracks,” will serve to verify the accuracy and the applicability of using each of their separated effects to predict each of their orientations. Compared to the low-frequency resistance of the plain matrix, the insulating cracks increased both the low-frequency and high-frequency resistances of the composites. The effect of the bridging conductive fibers, on the other hand, could be observed only through the high-frequency resistance, that was lower than the low-frequency resistance of the composites. Based on the intrinsic conductivity approach, the important parameters of the cracks and the fibers that determine the magnitude of change in the resistance are their aspect ratios, volume fractions, and their orientations with respect to the direction of measurement. Good agreements for the separated effects of each inclusion were obtained from the comparison of the measured AC-IS responses and the theoretical calculations. The understanding of the resistance change in the fiber-bridging area helps enable the use of AC-IS as a health-monitoring technique during the early stage of mechanical damage of the composites. It should be noted that although cement paste is used as the matrix material in the present work, the AC-IS approach established is equally applicable to other composites with moderately conductive matrix and within the dilute regime to avoid the percolation behavior of the inclusions.